Faktor-Faktor Penyebab Kenakalan Remaja di Lebak Mulyo Kecamatan Kemuning Kota Palembang - Andrianto Andrianto (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2019)
This research included in the research field (Field Resarch) is descriptive qualitative. As for informants here are 5 parents who have a child from a year 13-18 categorized 5 naughty teen teenager, 5 religious figures, public figures, 5 1 the head Lurah and 1 Chair RT. Whereas the collection of data in this study using the method observation, in-depth interviews and documentation. The analysis in this study uses data reduction techniques, presentation of data and verification.The study found that factors what causes juvenile delinquency in Lebak Mulyo Subdistrict Kemuning Palembang of which is the lack of attention to the elderly, the social environment is not good friends, hanging out and economic factors and efforts are being made to overcome parents ' juvenile delinquency in Lebak Mulyo Subdistrict Kemuning Palembang was by way of educating his son well, send in the religious school, giving Religious lessons, put his son in boarding school. Efforts are being made to overcome Neighborhood Party juvenile delinquency in Lebak Mulyo Subdistrict Kemuning Palembang was a teenager was given a briefing on religion, enlightenment, an appeal from Mr. RT so that people do not commit crimes khususya teens, created karangtaruna, futsal, sports programs are given the training, given the students if a less capable, given the youth, given the direction of religion, given the job that generates its own income and old people continued to flee into a more well, there should be a study of religious education, further enhance karang taruna, recitation and Assembly.